Blackwater Communal Septic Tank Domestic Waste Treatment into Clean Water with Multilevel Filter Method, Wetland, Lotus Fish Pond, Continued to Aquaponics IPAL in Terms of TSS and TDSA - K. Wulandari, Lies; Aditama, Vega; Setyobudiarso, Hery (KnE Social Sciences, 2023)
Blackwater or domestic waste is a type of liquid waste that requires adequate treatment so as not to pollute the environment. The effectiveness of wastewater treatment can be increased by using multilevel filters and aquatic plants as remediation agents. This study aims to improve the quality of communal domestic wastewater (WWTP) by reducing the value of domestic waste quality parameters. This study used an aquatic plant used as a Blackwater remediation agent, namely Roots Wangi (Vetiveria zizanoides). The independent variables in this study were plant distance, residence time, and plant root depth. The parameters observed were TSS (total suspended solid), TDS (total dissolved solid). The stratified filter consists of an arrangement of gravel, charcoal and sand, and the residence time is divided into a maximum of 60 days while waiting for the plants to thrive. The methods used are: Cleaning all WWTP ponds, preparing vetiver and hydroponic plants, preparing 3” PVC and holes, preparing multilevel filter gabions with weir mesh and plates, preparing multilevel filter materials, namely sand, gravel, and coconut shell charcoal. The implementation is: 3 multilevel filter packages, installation of fragrant root wetland plants in the 2nd pond, making fish and lotus ponds, aquaponics in WWTP. The data analysis method used is factor analysis. The results of the analysis show statistical similarities between vetiver plants and wastewater quality parameters, the formula is TSS = 142,395–1,865 * Wetland + e dan TDS = 1007,441–9,839 * Wetland + e. Therefore, it can be concluded that the use of multilevel filters, vetiver ponds, fish lotus ponds, aquaponics will significantly reduce the TSS and TDS parameters. Keywords: clean water, waste water, wetland, lotus fish pond